2017
DOI: 10.3197/096734017x14809635325593
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Edens on This 'Rivered Earth'? A Review Article on Water Management and Hydro-Resilience in the British Empire, 1860-1940s

Abstract: This article presents an overview of the management of fresh water in the British Empire from the 1860s to the 1940s. We argue that imperial water management shaped and responded to the imperatives of diverse ecologies and topographies, contrasting political and economic agendas and, not least, different colonial societies, technologies and lay expertise. Building on existing studies, we consider the broader ecological and social effects of water management on irrigated agriculture and cities as well as water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The central position of Western actors within colonial networks of transfer and exchange needs to be reconsidered-as objects of study as well as in terms of their respective authority and influence. The history of medicine and science has been the vanguard in this line of study, repeatedly demonstrating the importance of indigenous medical, agrarian, or technical expertise within networks of colonial knowledge, from quinine prophylaxis to channel construction [48,[89][90][91]. Much discussed in recent years, for example, was the "Black Rice" thesis.…”
Section: Exchanges Transfers and Network-writing Post/colonial Histories Of Technology And The Environment As Histories Of Entanglementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The central position of Western actors within colonial networks of transfer and exchange needs to be reconsidered-as objects of study as well as in terms of their respective authority and influence. The history of medicine and science has been the vanguard in this line of study, repeatedly demonstrating the importance of indigenous medical, agrarian, or technical expertise within networks of colonial knowledge, from quinine prophylaxis to channel construction [48,[89][90][91]. Much discussed in recent years, for example, was the "Black Rice" thesis.…”
Section: Exchanges Transfers and Network-writing Post/colonial Histories Of Technology And The Environment As Histories Of Entanglementsmentioning
confidence: 99%
“…After the introduction of piped water, residents actually became more vulnerable to water shortages than they had previously been. See also [89] on the hydro-resilience of pre/colonial landscapes and people. 23 This body of literature particularly highlights the ambivalent reactions to technical modernity and urban life in the Global South.…”
mentioning
confidence: 99%
“…As Parrinello's study suggests, interventions in hydrological regimes can exacerbate the impact of extreme weather events. In this regard, I have elsewhere advanced the concept of "hydro-resilience" to describe the ways in which colonial water control schemes had uneven impacts and unintended consequences, particularly for Indigenous peoples (Beattie & Morgan, 2017;Morgan, 2015). In British India, for example, engineering interventions "transformed the Orissa Delta from being a flooddependent agrarian regime into a flood-vulnerable landscape" (D'Souza, 2006, pp.…”
Section: Living With Water and Riskmentioning
confidence: 99%
“…In recent years, the wetlands in Louisiana [3], the dunes near New York [4], and the mangrove forests in the Philippines [5] have demonstrated that they too reduce the effects of coastal flooding. The growth in understanding of the natural environment, its benefits for human society [1,2], and the inequity of the expressed societal needs [6] is changing the field of hydraulic engineering. Hydraulic engineers increasingly need to use knowledge about the natural and the social environments in designing hydraulic infrastructures.…”
Section: Introductionmentioning
confidence: 99%